Antonio Gaudi - the great "Alchemist" of architecture - Sadykova Сара; Khairullina Эльмира (Рroblems of engineering and professional education, 2023)
This article is dedicated to a new approach to creativity of Antonio Gaudi. Here it is considered the features of his work and also the connection with alchemy. The author of the article analizes his creativity, shows the influence of alchemy on architecture, on formation of his unigue talent and high craft